Association of Cyclopropane Fatty Acid Synthesis with Thermo-Tolerance of Campylobacter Survival (Global Journal of Medical Research, 2022)
Aims To investigate the possession of the cyclopropane fatty acid synthase cfa gene by thermo-tolerant and non-thermo-tolerant Campylobacter spp and to examine the presence of the cfa gene in Campylobacter that survived the scalding stage of poultry processing and to further investigate the cfa gene expression at 37 C in different C jejuni strains that are able or not able to survive at 52 C Methods and Results The presence of the cfa gene in Campylobacter strains was determined by PCR In order to determine the effect of heating on survival the thermophilic C jejuni were grouped by those collected before and those collected after the scalding stage process both groups being exposed to 52 C Quantitative RT- PCR was performed to verify the gene expression level of cfa at 37 C in C jejuni strains able or not able to survive at 52 C
Keywords: campylobacter; cfa gene; heat tolerance; survival; poultry processing